A Comparison of Romanian Economy’s Macro Indicators with Other Countries That Have the Same Credit Score - YILMAZ ONUR ARİ (Global Economic Observer)
Credit Rating Agencies have become active promoter of neo-liberal policies since 1980s, and a strong credit rating plays an important role in determining the cost of borrowing. Although the transparency of credit rating agencies is discussed, the credit ratings given by these institutions shed light on the economies of the countries. These credit scores can be affected not only from economic factors, but also social and politic factors of a country. Romania has been given a credit score since 1996. According to 2018 ratings, Romania has been placed in lower medium grade countries category. This paper compares the macroeconomic indicators of countries in the lower medium grade category with Romania. This study also aims to determine whether the credit rating agencies consider the economic factors of a country objectively or act politically when they give a credit score. The results showed that Romania had a good performance at Total Debt/GDP ratio and relatively at interest rate, unemployment rate and real GDP growth rate, while it showed a bad performance at budget balance and inflation rate. According to the results, Romania had not the best or worst macroeconomic indicators in its category so it could be interpreted as credit rating agencies acted objectively by assessing Romania’s macroeconomic indicators and placed a deserved investible category.